Negative Bias During Early Attentional Engagement in Major Depressive Disorder as Examined Using a Two-Stage Model: High Sensitivity to Sad but Bluntness to Happy Cues - Ao, Xiang; Mo, Licheng; Wei, Zhaoguo; Yu, Wenwen; Zhou, Fang; Zhang, Dandan (Frontiers in Human Neuroscience, 2020)
Negative attentional bias has been well established in depression. However, there is very limited knowledge about whether this depression-relevant negative bias exits during initial attentional allocation, as compared to the converging evidence for the negative bias during sustained attention engagement. This study used both behavioral and electrophysiological measures to examine the initial attention engagement in depressed patients influenced by mood-congruent and incongruent emotions. The dot-probe task was performed with a 100-ms exposure time of the emotional cues (emotional and neutral face pairs). The behavioral results showed that the patients responded faster following valid compared to invalid sad facial cues. Electrophysiological indexes in the frame of the two-stage model of attentional modulation by emotions provided cognitive mechanisms in distinct attention engagement stages: 1) the patients exhibited reduced P1 amplitudes following validly than invalidly happy cues when compared to the healthy controls, indicating a positive attenuation at an early stage of automatic attention orientation; 2) the patients exhibited enhanced whereas the controls showed reduced P3 amplitudes following validly than invalidly sad cues, suggesting a mood-congruent negative potentiation in depression at the later stage of top-down voluntary control of attention. Depressed patients show a negative bias in early attentional allocation, reflected by preferred engagement with mood-congruent and diminished engagement with positive emotional cues/stimuli.